2010
DOI: 10.1016/j.nbt.2010.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plant growth regulators and genotype on the micropropagation of adult trees of Arbutus unedo L. (strawberry tree)

Abstract: Arbutus unedo grows spontaneously around the Mediterranean basin. The species is tolerant to drought and has a strong regeneration capacity following fires making it interesting for Mediterranean forestation programs. Considering the sparse information about the potential of this fruit tree to be propagated in vitro, a project to clone selected trees based on their fruit production was initiated a few years ago. The role of several factors on A. unedo propagation was evaluated. The results showed that 8.9 μm k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 23 publications
6
22
0
4
Order By: Relevance
“…unedo is, currently, undergoing an intense domestication process, with the commercialisation of improved genetic material (clones) to produce new plantations and the introduction of genetic material through seed from unknown origin [11,17]. Domestication together with growing climate change will affect the species’ natural resources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…unedo is, currently, undergoing an intense domestication process, with the commercialisation of improved genetic material (clones) to produce new plantations and the introduction of genetic material through seed from unknown origin [11,17]. Domestication together with growing climate change will affect the species’ natural resources.…”
Section: Discussionmentioning
confidence: 99%
“…Arbutus unedo fruit has strong antioxidant properties and it can be consumed fresh or processed, and it is used in Portugal to produce the liquor ‘aguardente’, an important source of income for land users, which has led to an on-going process of domestication of the species through clonal propagation of genotypes selected for fruit quality [15] and to the use of seeds from unknown origin. This species has economic importance to be used in Portugal and southern Europe, with different commercial uses from processed and fresh fruit production to ornamental, pharmaceutical and chemical industrial applications, due to the phenolic acids and terpenoid compounds with strong antioxidant activity, vitamin C and tannin content [15 and references therein, 16, 17]. Nevertheless, this species remains largely underutilized, and organizations such as FAO [18] developed efforts to increase the use of those species.…”
Section: Introductionmentioning
confidence: 99%
“…In A. officinalis maximum number of shoots was observed at 7.5 lM BA. The ideal concentrations of cytokinins differ from species to species and need to be estimated accurately to achieve the effective rates of multiplication (Gomes et al 2010). However, in A. officinalis increase in concentration of cytokinin in the medium favored growth and Bars denoted by the same letter within response variables are not significantly different (P = 0.05) using DMRT Rend.…”
Section: Discussionmentioning
confidence: 99%
“…Genotype influences shoot formation and rooting (Cezar et al, 2015). Gomes et al (2010) stated that the genotype of the donor plants is also a factor interfering with the multiplication. Also, Scaltsoyiannes et al (1998), observed that in Juglans regia, genotype plays a crucial role in micropropagation.…”
Section: Genotype Effect On Proliferation and Rooting Phasesmentioning
confidence: 99%